Efficient synthesis of azetidine-2,3-diones from L-(+)-diethyl tartrate - Chincholkar, Pinak M.; Puranik, Vedavati G.; Deshmukh, Abdul Rakeeb A. S. (Synlett, 2007)
A convenient route to enantiopure azetidine-2,3-diones is described. The chiral ketene generated from commercially available L-(+)-diethyl tartrate on Staudinger cycloaddition with different imines gave spiro-beta-lactams in good yields. These spiro-beta-lactams were transformed into azetidine-2,3-diones in excellent yields in a two-step process.
Keywords: Cycloaddition; imines; lactams; spiro compounds; stereoselective synthesis